1968
DOI: 10.1039/tf9686401113
|View full text |Cite
|
Sign up to set email alerts
|

Surface pressure and surface potential study of a synthetic phospholipid at the air/water interface

Abstract: Surface pressure and surface potential measurements on monolayers of synthetic 1,2-dipalrnitoylm-phosphatidylethanolamine at the air/water interface indicate that the axis of the zwitterion is parallel to the surface. Many two-dimensional arrangements in this plane are energetically possible. Surface phase dissociation constants of the zwitterion functional groups are calculated from surface potential data, and the effect on the monolayer of differing cations in the subphase is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1969
1969
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(16 citation statements)
references
References 4 publications
(1 reference statement)
2
14
0
Order By: Relevance
“…This is especiMly true for a micelle containing a zwitterionic surfactant such as acylcarnitine. This is supported by a large number of studies on zwitterionic surfactants (26)(27)(28)(29)(30) which indicate that these compounds tend to be oriented at interfaces with the line connecting the two charged portions lying parallel to the interface.…”
Section: Discussionmentioning
confidence: 80%
“…This is especiMly true for a micelle containing a zwitterionic surfactant such as acylcarnitine. This is supported by a large number of studies on zwitterionic surfactants (26)(27)(28)(29)(30) which indicate that these compounds tend to be oriented at interfaces with the line connecting the two charged portions lying parallel to the interface.…”
Section: Discussionmentioning
confidence: 80%
“…We presume the first, although impurity levels near 1% are difficult to quantify. Second, for pHϭ7Ϯ2 the polar head is uncharged, and therefore the surface pressure-area isotherms are not sensitive to small variations of pH or ionic milieu (Standish and Pethica, 1968). Third, the molecular area at high pressures, as deduced from the pressure-area isotherms, is given by the area of two aliphatic tails.…”
Section: B Phosphatidylethanolanolamines (Pe)mentioning
confidence: 99%
“…Figure 1A shows the compression curves for mixed cholesterol-dipalmitoyl cephalin monolayers spread on silica-free substrates of pH 6 at 20 ~ The pure cephalin monolayer exhibits a condensed film with a compressibility of 2.7 x 10 -3 cm. dyne -~ and a limiting area of 47 fk 2. molecule -z, which lies between the 45.2 A 2. molecule -1 reported by Standish and Pethica [13] on substrates containing 0.01 M NaCI, and the 49A 2 9 molecule -1 (Demel et al, [14]) or 48.3 A_ 2 9 molecule -1 (Hayashi et al, [15]) that have been found for films spread on substrates of pH 5.4. The mixed films likewise exhibited the liquid-condensed phase, with compressibilities of the same order as the pure cephalin and cholesterol films.…”
Section: Methodsmentioning
confidence: 83%